Heavy training stress in male rowers: Effects on circulatory responses and mood state profiles - Jürimäe, J.; Purge, P.; Mäestu, J.; Jürimäe, T. (Kinesiology, 2004)
The effects of short-term overreaching on the circulatory responses and mood state parameters were investigated in male rowers. Fourteen national team level rowers (18.6 ± 2.0 yrs; 186.9 ± 5.7 cm; 82.4 ± 6.9 kg) were monitored during a six-day training camp. The training regimen consisted mainly of low-intensity on-water rowing and resistance training, for 19.2 ± 3.9 h, corresponding to an approximate 100% increase in the training load. The 2,000 m rowing ergometer performance time increased from 395.9 ± 10.8 to 404.2 ± 11.9 s corresponding to a mean power of 361.9 ± 28.5 and 349.0 ± 32.8 W, respectively. Blood lactate concentration measured five minutes after the test (from 19.2 ± 2.9 to 16.2 ± 2.3 mmol.l-1) and mean heart rate (from 184.6 ± 7.5 to 179.2 ± 7.4 beats/min-1) decreased. Maximal oxygen consumption remained unchanged. The subjective ratings of fatigue and muscle soreness increased and were related to the training volume (r>0.52). The blood parameters of the red blood cell count, hemoglobin concentration and hematocrit were decreased, while blood and plasma volumes were increased after the training period. The blood variables were not correlated with the training volume (r<-0.44; p>0.05). The change between tests in the corresponding heart rate demonstrated correlation to the changes in blood (r=-0.48) and plasma (r=-0.55) volumes. It is concluded that the most appropriate and simple tool for monitoring a short-term overload training period is the self-reported ratings of well-being on a daily basis.